Hybrid persulfate/sonocatalysis for degradation of acid orange 7 in the presence of Ag2O/CuWO4 composite: Operating parameters and sonocatalytic mechanism. (25th March 2023) - Liu, Yang-Cheng; Liu, Xuan; Wang, Xin; Li, Zi-Hao; Chen, Chang-Lan; Xiang, Zheng
Abstract: A series of Ag2 O/CuWO4 composite catalysts were constructed and the effects, parameters and mechanisms of their sonocatalytic degradation of acid orange 7 (AO7) and hybrid persulfate/sonocatalysis for degradation of AO7 were studied. Ag2 O/CuWO4 composite catalysts were constructed by coprecipitation method. The crystal characteristics, surface element composition, valence state and electrochemical characteristics, etc. of the composite were characterized by relevant instruments. The sonocatalytic process of Ag2 O/CuWO4 composite catalyst was studied and optimized. Under the condition of ultrasonic power of 500 W, AO7 solution with initial concentration of 15 mg/L was sonocatalytic degraded for 1 h by Ag2 O/CuWO4 (1:10) composite catalyst (adding amount of 1 g/L), and the degradation effect was the best, with the maximum degradation rate of 84.97 ± 2.23%. When persulfate was combined with sonocatalysis, the degradation rate of AO7 continued to increase to 99.01 ± 0.04% after 15 min of reaction. Compared with the single action, it not only improved the efficiency but also improved the effect. The trapping experiment showed that the active substances generated during the sonocatalytic degradation of AO7 by Ag2 O/CuWO4 included hydroxyl radical, holes and superoxide anion radical. Based on this, the mechanism of sonocatalytic degradation was proposed. At the same time, Ag2 O/CuWO4 composite catalyst showed good stability and reusability for recycling, which has the potential for further industrial development and application. Graphical abstract: Image 1 Highlights: Ag2 O/CuWO4 composite catalyst with good sonocatalytic activity on the degradation of AO7 were synthesized. The synthesized Ag2 O/CuWO4 composite catalyst was characterized and its catalytic mechanism was studied. The sonocatalytic degradation of AO7 was carried out with Ag2 O/CuWO4 composite catalyst as catalyst. The optimum conditions of AO7 degradation under ultrasound were optimized, and better treatment effect was achieved by combining persulfate.